SNAKE BITE: TREATMENT SEEKING BEHAVIOUR AMONG SINDH RURAL POPULATION - Chandio, Atta Muhammad; Sandelo, Pervaiz; Rahu, Ali Akbar; Ahmed, S. Tousif; Dahri, Amir Hamzo; Bhatti, Rashida (Journal of Ayub Medical College Abbottabad, 2000)
Background: Snake bite is a common medical emergency in Sindh rural and the epidemiological features and management of the cases vary from region to region. This survey was conducted to see the community practices regarding the management of snake bite cases. Methods: We conducted a community based survey from 200 villages from six different districts of Sindh. Results: 74.5% of snake bite cases seek the treatment from local doctors while 25.5% use the other measures. 92% of the cases use different First Aid measures while 8% were not using any First Aid measures. 55.5% of the people know about the Anti Snake Venom (ASV) white 45.5% do not know about it. Only 49% of the people were using different preventive measures against snake bite.